Clinical effects and safety of treating diabetic macular edema with intravitreal injection of ranibizumab combined with retinal photocoagulation - Yan PS; Qian C; Wang WZ; Dong Y; Wan GM; Chen Y (Dove Medical Press, 2016)
Panshi Yan, Cheng Qian, Wenzhan Wang, Yi Dong, Guangming Wan, Yue Chen Department of Ophthalmology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China Background: This study was designed to examine the clinical effects of treating diabetic macular edema with an intravitreal injection of ranibizumab in combination with retinal photocoagulation.Methods: Sixty-two cases (75 eyes) with confirmed severe proliferative diabetic retinopathy or proliferative diabetic retinopathy in combination with macular edema were randomly divided into the observation group (37 eyes were given an intravitreal injection of ranibizumab combined with retinal photocoagulation) and the control group (38 eyes received retinal photocoagulation only). Vision, fundus condition, central macular thickness, and the macular leakage area were recorded before and after treatment.Results: The best-corrected visual acuity and macular leakage area were similar between the observation and control groups (P>0.05). The best-corrected visual acuity in the observation group was higher than that in the control group 3 and 6 months after treatment (P<0.05) and showed a rising tendency. The macular leakage area in the observation group was significantly lower than that in the control group 1 and 3 months after treatment (P<0.05). However, the macular leakage area was similar 6 months after treatment (P>0.05). The central macular thickness of the observation group was lower than that in the control group 1, 3, and 6 months after treatment (P<0.05). The laser energy used in the observation group was also smaller than that in the control group (P<0.05). The intraocular pressure was not significantly different between the groups (P<0.05). No patients in the two groups developed eye or systemic complications, such as glaucoma, cataract, or vitreous hemorrhage during treatment. Conclusion: Intravitreal injection of ranibizumab combined with retinal photocoagulation was proven to be effective in treating diabetic macular edema as it improved vision and resulted in fewer complications. Keywords: vitreous body, ranibizumab, photocoagulation, diabetic macular edema